2000
DOI: 10.1124/mol.58.5.1100
|View full text |Cite
|
Sign up to set email alerts
|

Polyanionic (i.e., Polysulfonate) Dendrimers Can Inhibit the Replication of Human Immunodeficiency Virus by Interfering with Both Virus Adsorption and Later Steps (Reverse Transcriptase/Integrase) in the Virus Replicative Cycle

Abstract: Polyanionic dendrimers were synthesized and evaluated for their antiviral effects. Phenyldicarboxylic acid (BRI6195) and naphthyldisulfonic acid (BRI2923) dendrimers were found to inhibit the replication of human immunodeficiency virus type 1 (HIV-1; strain III(B)) in MT-4 cells at a EC(50) of 0.1 and 0.3 microg/ml, respectively. The dendrimers were not toxic to MT-4 cells up to the highest concentrations tested (250 microg/ml). These compounds were also effective against various other HIV-1 strains, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
141
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(142 citation statements)
references
References 21 publications
1
141
0
Order By: Relevance
“…The resulting amines were modified with sodium 3,6-disulfonaphthyl isothiocyanate or 3,5-dicarboxyphenyl isothiocyanate to form polysulfate or polycarboxylate functionalized dendrimers (18,19), respectively. [83] The polysulfate functionalized PAMAM dendrimers (19) showed to be effective against HIV-1 and HIV-2 with efficacies similar to those observed with dextran sulfate (1). Additionally, the polysulfate dendrimers were also effective against HIV strains that were resistant to 1 and AMD-3100 (bicyclam derivative that is a candidate CXCR4 antagonist).…”
Section: Dendritic Polymer-based Entry Inhibitorsmentioning
confidence: 83%
See 1 more Smart Citation
“…The resulting amines were modified with sodium 3,6-disulfonaphthyl isothiocyanate or 3,5-dicarboxyphenyl isothiocyanate to form polysulfate or polycarboxylate functionalized dendrimers (18,19), respectively. [83] The polysulfate functionalized PAMAM dendrimers (19) showed to be effective against HIV-1 and HIV-2 with efficacies similar to those observed with dextran sulfate (1). Additionally, the polysulfate dendrimers were also effective against HIV strains that were resistant to 1 and AMD-3100 (bicyclam derivative that is a candidate CXCR4 antagonist).…”
Section: Dendritic Polymer-based Entry Inhibitorsmentioning
confidence: 83%
“…Additionally, the polysulfate dendrimers were also effective against HIV strains that were resistant to 1 and AMD-3100 (bicyclam derivative that is a candidate CXCR4 antagonist). [83] Compared to the polysulfate functionalized PAMAM dendrimers, the polycarboxylate functionalized PAMAM dendrimers (19) were equally effective for HIV-1 but significantly less effective against strains of HIV-2. Analogous to dendrimers based on PAMAM, a 4 th generation poly(L-lysine) dendrimer modified with 32 3,6-disulfonaphthyl groups (20) has shown to be an effective inhibitor against infection of various clades of HIV-1.…”
Section: Dendritic Polymer-based Entry Inhibitorsmentioning
confidence: 99%
“…Owing to the different cell penetration rates of BRI6195 and BRI2923 compounds, the latter was demonstrated to exhibit another antiviral activity during reverse transcription and integration steps. Unfortunately, it has been found that some gp120 mutations display inconsistency, preventing the described PAMAM dendrimers from completely and successfully curing patients after treating cells [Witvrouw, 2000].…”
Section: Dendrimers Themselves As Anti-hiv Therapeutic Agentsmentioning
confidence: 99%
“…As far as dendrimers are concerned, their applications in treatment of several human diseases are under critical investigation and looks very promising; these macromolecules serve as targeted drug, carriers and delivery agents as well as imaging agents in human systems [4][5][6]. In particular, polymers having a dendrimer-based structure have emerged from several research programs focused on the development of inhibitors of HIV and other enveloped viruses [7][8][9][10][11][12][13][14][15][16][17][18][19].…”
Section: IImentioning
confidence: 99%